The inflammability of suburban pine recreational forests near Krasnoyarsk - P. A. Tsvetkov; I. V. Putintseva (Сибирский лесной журнал, 2018)
Increasing urbanization makes people study the environmental and sanative functions of suburban forests. Forest attendance of over two thousand people per day per hectare in a season is facilitated by a dense network of roads and trails in suburban forests near Krasnoyarsk, so that residents can penetrate into forest interiors. Over recent years the scale of recreational forest usage is constantly increasing. Currently, uncontrolled recreational use of forests prevails. Fires are often human-caused. In the paper an assessment of relative inflammability of suburban recreational pine forests near Krasnoyarsk is provided. An analysis of the distribution of forest fires by the months of fire season and origins of their occurrence was made. An objective indicator of the inflammability norms for each particular year and the methodology for their calculation were proposed. The calculation of the normative level of the maximum burned areas for different classes of fire hazard according to weather conditions is presented. These studies are necessary to justify the level of forest protection for fire seasons of different severity, which is characterized by the number of days with III–V classes of fire hazard according to weather conditions. The maximum burned area of forest fires calculated for long-term data could be also served as the basis for assessing the effectiveness of forest protection.